2007
DOI: 10.1007/s00531-007-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

The Meso-Cenozoic thermo-tectonic evolution of the Eastern Pyrenees: an 40Ar/39Ar fission track and (U–Th)/He thermochronological study of the Canigou and Mont-Louis massifs

Abstract: Vertical displacements on the SW-NE Têt fault (Eastern Pyrenees Axial Zone, France), which separates the Variscan Canigou-Carança and Mont-Louis massifs, were constrained using a thermochronologic multi-method approach. 40 Ar/ 39 Ar data from the granitic Mont-Louis massif record its Variscan cooling history and reveal no ages younger than Early Cretaceous, while the CanigouCarança gneiss massif records systematically younger 40 Ar/ 39 Ar ages. These younger 40 Ar/ 39 Ar ages in the Canigou-Carança gneiss mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
125
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(152 citation statements)
references
References 61 publications
25
125
2
Order By: Relevance
“…In the last decades, several works (Vanara et al, 1997;Vanara, 2000;Perez-Vila et al, 2001;Agustí et al, 2006;Calvet and Gunnell, 2008;Lacan, 2008;Ortuño, 2008;Suc and Fauquette, 2012;Ortuño et al, accepted) have reported postorogenic surface uplift > 0.5 km and up to 2 km since the late Miocene at several sites, all located at the High Chain. The same occurs with the data on post-orogenic enhanced exhumation (Fitzgeral et al, 1999;Calvet and Gunnell, 2008;Maurel et al, 2008;Gunnell et al, 2008;Metcalf et al, 2009;Méresse, 2010), which can be owed to the surface uplift and/or enhanced erosion.…”
Section: Neotectonic Modelmentioning
confidence: 65%
See 2 more Smart Citations
“…In the last decades, several works (Vanara et al, 1997;Vanara, 2000;Perez-Vila et al, 2001;Agustí et al, 2006;Calvet and Gunnell, 2008;Lacan, 2008;Ortuño, 2008;Suc and Fauquette, 2012;Ortuño et al, accepted) have reported postorogenic surface uplift > 0.5 km and up to 2 km since the late Miocene at several sites, all located at the High Chain. The same occurs with the data on post-orogenic enhanced exhumation (Fitzgeral et al, 1999;Calvet and Gunnell, 2008;Maurel et al, 2008;Gunnell et al, 2008;Metcalf et al, 2009;Méresse, 2010), which can be owed to the surface uplift and/or enhanced erosion.…”
Section: Neotectonic Modelmentioning
confidence: 65%
“…This last event could be responsible from a rapid post-orogenic uplift of the Eastern Pyrenees reported by different authors (Pérez-Vila et al, 2001;Agustí et al, 2006;Suc and Fauquette, 2012) and possibly reflected in the exhumation history of the area Maurel et al, 2008).…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-temperature history (burial, heating and cooling) during the initial accretionary stage are therefore largely unknown. It may involve underestimated competing cooling processes such as syn-orogenic thermal relaxation or cooling by underthrusting as suggested recently in Taiwan (Mesalles et al, 2014).…”
Section: Hyper-extension In the Pyrenees And Thermal Constraintsmentioning
confidence: 96%
“…Briais et al [59] and Calvet [60] attribute the triangular facets of the Têt fault scarp to its recent normal activity, while Petit and Mouthereau [61] suggest they are actually the morphological expression of the CMNC corroborating with the differential erosion of the hosting rocks. Authors agree that current displacements are low or nonexistent [56,57,60,[62][63][64]. The general tectonic regime seems to have changed during the Pliocene from normal [58,64,65] to reverse, but with no clear evidence about the compressive or strike-slip nature of the stress tensor [58].…”
Section: Geological Settingmentioning
confidence: 99%